THE MYTH OF SELF-DIAGNOSIS: A STUDY OF STUDENTS IN MEDAN’S PUBLIC UNIVERSITIES ON MISCONCEPTIONS AND DIGITAL REALITY - Permana, Adhitya Bima; Sazali, Hasan (International Journal of Cultural and Social Science, 2025)
The phenomenon of self-diagnosis has become increasingly prevalent among university students, particularly in Medan, Indonesia, where digital information is widely accessible. This study highlights the importance of investigating self-diagnosis practices among students in a local context characterised by diverse socio-cultural backgrounds and a high level of social media usage. The research aims to explore students’ perceptions, focusing on how self-diagnosis affects their mental health and the patterns of acceptance formed around it. A qualitative approach with a phenomenological method was employed, involving in-depth interviews with ten purposively selected students from public universities in Medan. Thematic coding was used to analyse the data, guided by Stuart Hall’s audience reception theory, categorising students into dominant, negotiation, and opposition groups. Findings reveal that students with dominant acceptance readily trust unverified online mental health content, while those in negotiation display partial acceptance with cautious evaluation, and the opposition group critically rejects such content in favour of professional consultation. The study contributes to the existing literature by integrating social and digital contexts in understanding self-diagnosis practices and proposes the development of educational interventions and policy recommendations to improve students' critical engagement with digital mental health information.